3D modeling of chromatin structure: is there a way to integrate and reconcile single cell and population experimental data?. (10th April 2017) - Le Dily, François; Serra, François; Marti‐Renom, Marc A.
Abstract : The genome is organized in a hierarchical fashion within the nucleus in interphase. This nonrandom folding of the chromatin fiber is thought to play important roles in the processing of the genetic information. Therefore, a better knowledge of the mechanisms underlying the three‐dimensional structure of the genome appears essential to fully understand the nuclear processes including transcription and replication. Fluorescent in situ hybridization (FISH) and molecular biology methods deriving from the Chromosome Conformation Capture technique are the methods of choice to study genome 3D organization at different levels. Although these single cell and population methods allowed to highlight similar chromatin structures, they also show frequent discrepancies which might be better understood by improving the capacity to generate actual 3D models of organization based on the different types of data available. This review aims at giving an overview of the principles, advantages, and limits of microscopy and molecular biology methods of analysis of genome structure and at discussing the different approaches of modeling of chromatin classically used and the improvements that are necessary to reach a better understanding on the links between chromatin structure and its spatial organization. WIREs Comput Mol Sci 2017, 7:e1308. doi: 10.1002/wcms.1308 This article is categorized under: Structure and Mechanism > Molecular Structures Molecular and Statistical Mechanics > Molecular Interactions Software > Molecular Modeling Abstract : Graphical comparison of the two orthogonal ways of interrogating the genome three‐dimensional structure. Left panel depicts frequency of cross‐linking with respect the genomic distance of the interacting loci in a typical 3C‐based experiment. Right panel represents a typical image from light microscopy depicting distance of loci in a chromosome.